Review: Solubility And Bioavailability Enhancement Of Carvedilol Using Multicomponent Crystal Method - Nadiyah Salma Athaya; Iyan Sopyan (Indonesian Journal of Pharmaceutics, 2022)
Carvedilol is included in the BCS class 2 classification, drugs that have low solubility and high permeability. Drugs with low solubility pose a major challenge for oral drugs in achieving the desired systemic circulation. Moreover, carvedilol is indicated for the treatment of cardiovascular disease and hypertension which requires a rapid pharmacological response. A way to increase drug solubility is by forming multicomponent crystals, including solvates, cocrystals, and salts. Cocrystal and salt formation methods are the most frequently used methods in the pharmaceutical field. The multicomponent crystal approach is a process of combining active drug ingredients with other compounds known as coformers which then interact through molecular bonds. Multicomponent crystals provide benefits to improve the physicochemical properties of drugs without affecting their pharmacological properties. In this review, we discuss the multicomponent crystal approach as an effort to increase the solubility and bioavailability of carvedilol. The main reference data used in this review are research journals published in the last 10 years (2012-2022) using the keywords carvedilol, multicomponent crystal, solubility, bioavailability, and using Google Scholar as a database. There is also a discussion on regulation of cocrystals, methods for forming multicomponent crystals, and characterization of multicomponent crystals. The multicomponent crystal approach has promising benefits in increasing the solubility and bioavailability of carvedilol in the body. Keywords: Carvedilol, multicomponent crystal, solubility, bioavailability